2016
DOI: 10.1007/s13410-016-0491-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of yeast in diabetic foot infections

Abstract: Diabetic foot infections are a serious threat which cause a long term of hospitalization of diabetes patients and lead to amputations. Hence, prompt diagnosis is an important criterion in the treatment of these infections. This study was carried out to determine the prevalence of yeast in diabetic foot infections. The pus samples were collected from patients presenting with diabetic foot ulcer and processed for microbiological investigation. The patients investigated comprised of 82 males and 78 females. Most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
(26 reference statements)
1
1
1
Order By: Relevance
“…The low incidence of resistance to amphotericin B in our study and previous similar studies could be explained by the fact that the agent is not commonly used among diabetic patients due to hypokalemia-associated nephrotoxicity. Our findings contrasts with those from other studies done in different parts of the world that reported up to 100% susceptibility rate of amphotericin B to Candida species [ 38 - 41 ]. Resistance to polyenes in Candida species may be associated with defective C5, 6-desaturase functionality in C. albicans and mutation of ERG 2, 3, 5, 6 and 11 genes involved in ergosterol cell membrane synthesis.…”
Section: Discussioncontrasting
confidence: 99%
“…The low incidence of resistance to amphotericin B in our study and previous similar studies could be explained by the fact that the agent is not commonly used among diabetic patients due to hypokalemia-associated nephrotoxicity. Our findings contrasts with those from other studies done in different parts of the world that reported up to 100% susceptibility rate of amphotericin B to Candida species [ 38 - 41 ]. Resistance to polyenes in Candida species may be associated with defective C5, 6-desaturase functionality in C. albicans and mutation of ERG 2, 3, 5, 6 and 11 genes involved in ergosterol cell membrane synthesis.…”
Section: Discussioncontrasting
confidence: 99%
“…(27) The results of our study showed that the prevalence of dermatomycosis tends to be higher in uncontrolled diabetic patients than in controlled ones. This result is in concordance with Sugandhi et al (28) in that poor glycemic control was significantly associated with fungal infection. Type 2 diabetes was previously known as predisposing factor for fungal infection especi al l y Candida infection and dermatophytosis of the foot and nail.…”
Section: Discussionsupporting
confidence: 93%
“…Rasoulpoor et al reached a similar finding in their systematic review analysis, stating that the rate of fungal infection in DFU was higher in elderly individuals [12]. Another study published in 2017 by Sugandhi and Prasanth found that patients in the 51-60 years old age group were more susceptible to fungal infection in DFU due to their physical health conditions [13]. Diabetes duration also acts a vital function in the creation of diabetic foot ulcer and the increase in the occurrence of fungal infection.…”
Section: Discussionmentioning
confidence: 63%